2018
DOI: 10.1002/2017jd027821
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Lightning Within Electrified Snowfall Events Using Lightning Mapping Arrays

Abstract: This study examined 34 lightning flashes within four separate thundersnow events derived from lightning mapping arrays (LMAs) in northern Alabama, central Oklahoma, and Washington DC. The goals were to characterize the in‐cloud component of each lightning flash, as well as the correspondence between the LMA observations and lightning data taken from national lightning networks like the National Lightning Detection Network (NLDN). Individual flashes were examined in detail to highlight several observations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 53 publications
7
38
0
Order By: Relevance
“…Another item of interest is that about 20% of CG snow lightning has positive flashes, which is more than twice when compared to warm CG lightning flashes (8%, Table ). This fits with recent analysis by Schultz et al (), which showed that 21 of the 30 flashes observed in their thundersnow study were negative (70%), while remaining 30% flashes were positive. Pettegrew () showed that about 8% of the thundersnow lightning flashes were positive based on a 14‐storm study over the central United States.…”
Section: Resultssupporting
confidence: 93%
“…Another item of interest is that about 20% of CG snow lightning has positive flashes, which is more than twice when compared to warm CG lightning flashes (8%, Table ). This fits with recent analysis by Schultz et al (), which showed that 21 of the 30 flashes observed in their thundersnow study were negative (70%), while remaining 30% flashes were positive. Pettegrew () showed that about 8% of the thundersnow lightning flashes were positive based on a 14‐storm study over the central United States.…”
Section: Resultssupporting
confidence: 93%
“…If only referring to the vertical arrangements of the charge regions included in discharges, the charge structures contained quad‐polar structures (Figures a1 and b2; the charges from top to bottom were positive, negative, positive, and negative), tripolar structures (Figures a2 and b3; upper positive, middle negative, and lower positive), dipolar structures (Figures b1 (the main part), 21c1, 21c2, and 21c3; upper positive and lower negative), inverted dipolar structures (Figures a4, c4, and c5; upper negative and lower positive) and inverted tripolar structures (Figures a3, b4, b5, and c6; upper negative, middle positive, and lower negative). In contrast, in most previous studies, winter thunderstorms were suggested to have dipolar or tripolar charge structures (Brook et al, ; Caicedo et al, ; Kumjian & Deierling, ; Schultz et al, ; Takahashi et al, , , ), which was similar to normal summer thunderstorms (Williams, ). As we mentioned in the beginning of section , due to the limit of the observation range of the LMA and the rapid movement of thunderstorms, the cells producing the investigated flashes might be in different development stages; therefore, the diverse patterns of the charge distributions, as shown in sections – and summarized in Figure , might have resulted from both the differences in diverse cells and distinct evolution stages.…”
Section: Summary and Discussionmentioning
confidence: 72%
“…The LMA sources can only indicate the charge regions taking part in lightning discharges, which is more different from the observations of sounding through the storm (e.g., Takahashi et al, 1999Takahashi et al, , 2017Takahashi et al, , 2018 (Figures 21a3, 21b4, 21b5, and 21c6; upper negative, middle positive, and lower negative). In contrast, in most previous studies, winter thunderstorms were suggested to have dipolar or tripolar charge structures (Brook et al, 1982;Caicedo et al, 2018;Kumjian & Deierling, 2015;Schultz et al, 2018;Takahashi et al, 1999Takahashi et al, , 2017Takahashi et al, , 2018, which was similar to normal summer thunderstorms (Williams, 1989). As we mentioned in the beginning of section 3, due to the limit of the observation range of the LMA and the rapid movement of thunderstorms, the cells producing the investigated flashes might be in different development stages; therefore, the diverse patterns of the charge distributions, as shown in sections 3.1-3.3 and summarized in Figure 21, might have resulted from both the differences in diverse cells and distinct evolution stages.…”
Section: Charge Structurementioning
confidence: 64%
See 1 more Smart Citation
“…Within the context of another measurement campaign in the US planes, the Severe Thunderstorm Electrification and Precipitation Study (STEPS) (Lang et al, 2004), observations were presented about storms with normal and inverted polarity (Tessendorf et al, 2007). More recently, Kumjian and Deierling (2015) and Schultz et al (2018) examined lightning-producing snow storms.…”
Section: Introductionmentioning
confidence: 99%